Prostate high dose-rate brachytherapy as monotherapy for low and intermediate risk prostate cancer: Efficacy results from a randomized phase II clinical trial of one fraction of 19 Gy or two fractions of 13.5 Gy. (May 2020) - Morton, Gerard; McGuffin, Merrylee; Chung, Hans T.; Tseng, Chia-Lin; Helou, Joelle; Ravi, Ananth; Cheung, Patrick; Szumacher, Ewa; Liu, Stanley; Chu, William; Zhang, Liying; Mamedov, Alexandre; et al.
Highlights: HDR monotherapy as 13.5 Gy × 2 is highly effective for low and intermediate risk prostate cancer. Single fraction HDR monotherapy has high local failure rate and should not be used. HDR monotherapy has low toxicity. Abstract: Background and purpose: High dose-rate (HDR) brachytherapy as monotherapy is a treatment option for localized prostate cancer, but optimal dose and fractionation is unknown. We report efficacy results of a randomized phase II trial of HDR monotherapy delivered as either one or two fractions. Materials and methods: Eligible patients had low or intermediate risk prostate cancer, prostate volume <60 cc, and no androgen deprivation use. 170 patients were randomized to receive HDR as either a single fraction of 19 Gy or as two fractions of 13.5 Gy one week apart. Median age was 65 years, median PSA was 6.33 ng/ml, and Grade Group 1, 2 and 3 was present in 28%, 60%, and 12%, respectively. There was no difference in baseline factors between arms and 19%, 51% and 30% had low risk, favourable intermediate and unfavourable intermediate risk disease, respectively. The Phoenix definition was used to define biochemical failure, all local failures were confirmed by biopsy and toxicity was assessed using CTCAE v.4. Results: Median follow-up was 60 months. PSA decreased more quickly in the 2-fraction arm ( p  = 0.009). Median PSA at 5-years was 0.65 ng/ml in the single fraction and 0.16 ng/ml in the 2-fraction arm. The 5-year biochemical disease-free survival and cumulative incidence of local failure was 73.5% and 29% in the single fraction arm and 95% ( p  = 0.001) and 3% ( p  < 0.001) in the 2-fraction arm, respectively. Recurrence was not associated with initial stage, grade group, or risk group. Grade 2 late rectal toxicity occurred in 1% while the incidence of grade 2 and 3 urinary toxicity was 45% and 1%, respectively, with no difference between arms. Conclusions: HDR monotherapy delivered as two fraction of 13.5 Gy is well tolerated with a high cancer control rate at 5 years. Single fraction monotherapy is inferior and should not be used.